Pattern of Bacterial Pathogens In Burn Wound Infections In Ibadan, Nigeria (2004)
A retrospective study of 85 patients with burn wound infections was carried out in University College Hospital, Ibadan, Nigeria, between April 1998 and March 2001. A total number of 85 specimens consisting of 35 wound swabs (41.2%) and 50 wound biopsies (58.8%) were processed during the period. Burn wound infections were significantly more frequent in children and adolescents (5-20 yr) than in adults (p < 0.05). Klebsiella species was the pathogen most commonly isolated, constituting 34.4%. This was closely followed by Pseudomonas aeruginosa (29.0%) and Staphylococcus aureus (26.8%). The rate of isolation of Gram-negative organisms was more than twice that of Gram-positive organisms. More than 75% of the Gram negative isolates were resistant to gentamicin, a commonly used antibiotic for Gram-negative infections, but sensitive to ceftazidime and pefloxacin. Gram-positive isolates were predominantly Staphylococcus aureus sensitive to azithromycin and pef- loxacin. This study highlights the predominant bacterial pathogens and their antimicrobial profile among infected burn wounds in our centre.